Jahrestagung der Gesellschaft für Interlinguistik e.V. Berlin, 10‑12.11.2017 - Brosch, Cyril Robert (Język. Komunikacja. Informacja, 2019)
Jahrestagung der Gesellschaft für Interlinguistik e.V. Berlin, 10‑12.11.2017